Eo-Oligocene Oil Shales of the Talawi, Lubuktaruk, and Kiliranjao Areas, West Sumatra: Are they potential source rocks? - Iqbal, M.; Suwarna, Nana; Syafri, Ildrem; Winantris, Winantris (Geological Agency, 2014)
DOI:10.17014/ijog.v1i3.198To anticipate the increasing energy demand, additional data and information covering unconventional fossil fuels such as oil shale must be acquired to promote the usage of alternative energy sources to crude oil. The Talawi and Lubuktaruk regions situated within intra-montane Ombilin Basin, and the Kiliranjao assumed to be a small intra montane basin are occupied by Eo-Oligocene sediments of Sangkarewang and Kiliran Formations, respectively. Field activity, geochemical screening techniques, and organic petrographic analysis, supported by SEM mode, are methods used. Most of the oil shale sequence is typically of an organically rich-succession comprising predominantly well-bedded, laminated and fissile, brownish to dark grey organic-rich shale and mudstone rocks. The exinite macerals within oil shale comprise mainly Pediastrum-lamalginite with minor cutinite, resinite, liptodetrinite, sporinite, bituminite, and rare Botryococcus-telalginite. Therefore; the oil shale deposits can be described as â€œlamositesâ€. Minor vitrinite maceral is also recognized. TOC analysis on selected shale samples corresponds to a fair up to excellent category of source rock characterization. The hydrogen index (HI) for all samples shows a range of values from 207 - 864, and pyrolysis yield (PY) ranges from 2.67 to 79.72 mg HC/g rock. The kerogen is suggested to be of mixed Type II and Type I autochthonous materials such as alginite, with minor allochthonous substances. Oil samples collected appear to be positioned within more oil prone rather than gas prone. Thermal maturity of the oil shales gained from Tmax value and production index (PI) tends to show immature to marginally/early mature stage. A consistency in the thermal maturity level results by using both Tmax and vitrinite reflectance value is recognized. On the basis ofÂ SEM analysis, the oil shale has undergone a late eodiagenetic process. Thereby, overall, vitrinite reflectance agreeing with Tmax rates, are also consistent with the PI (production index) values and SEM result. By evaluating all the results of geochemical and organic petrological analyses conducted on shale lithologies (shale and mudstone), it can be concluded that the oil shales in those areas have a favourable potential for generation of shale oil or gas to be included as alternative energy resources in the future.